1998
DOI: 10.1007/s11661-998-0325-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of SiC volume fraction and particle size on the fatigue resistance of a 2080 Al/SiC p composite

Abstract: The effect of SiC volume fraction and particle size on the fatigue behavior of 2080 Al was investigated. Matrix microstructure in the composite and the unreinforced alloy was held relatively constant by the introduction of a deformation stage prior to aging. It was found that increasing volume fraction and decreasing particle size resulted in an increase in fatigue resistance. Mechanisms responsible for this behavior are described in terms of load transfer from the matrix to the high stiffness reinforcement, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
107
2
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 242 publications
(131 citation statements)
references
References 38 publications
10
107
2
2
Order By: Relevance
“…Microcracks were always initiated at the particle-matrix interfaces where an Al 2 O 3 whisker was also located very near to the crack initiated SiC particle (marked by W 1 in Figure 4). Previous researches reported that the main reason of microcrack initiation in the particulate or whisker reinforced system is debonding at the reinforcement-matrix interface [6,28,29]. The results obtained for hybrid MMC are consistent with these observations.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Microcracks were always initiated at the particle-matrix interfaces where an Al 2 O 3 whisker was also located very near to the crack initiated SiC particle (marked by W 1 in Figure 4). Previous researches reported that the main reason of microcrack initiation in the particulate or whisker reinforced system is debonding at the reinforcement-matrix interface [6,28,29]. The results obtained for hybrid MMC are consistent with these observations.…”
Section: Resultssupporting
confidence: 87%
“…However in practice, it is often difficult to obtain a homogeneous distribution of reinforced particles or whiskers. Further, it has been found that the non-uniformity in the reinforcement arrangement can have significant effects on the mechanical properties of the MMCs [6,7]. Existing experimental and theoretical evidences suggest that the homogeneity of particles or whiskers spatial arrangement plays a key role in controlling the yield strength, ductility, fatigue and fracture behaviors of MMCs [8].…”
Section: Introductionmentioning
confidence: 99%
“…The results of experimental data support this statement and reveal that the distribution of the reinforcing particles and the randomness pattern of the constituents can greatly influence the mechanical behavior of the composites (Chawla et al, 1998;Watt et al, 1996). Through extensive observations it is revealed agglomeration and network formation of the particles are responsible for the high levels of reinforcement, and also the breakdown of networks and the deagglomeration are the main source of the non-linear responses of strain (Heinrich et al, 2002;Kraus, 1984).…”
Section: Introductionsupporting
confidence: 52%
“…Lloyd D.J et al [3] studied the effect of particle induced damage in MMCs, with MMCs reinforced by particles with a size greater than 10µm, the dominant damage mechanism was cracking of particle and that the particle -matrix interface appeared to have little effect on the overall damage fracture behaviour. Chawla et al [4] showed that in 2080/SiC p composites with volume fractions ranging from 10 to 30 vol. %, particle cracking was observed above an average particle size of 20 µm.…”
Section: Literaturementioning
confidence: 99%